Fluconazole Population Pharmacokinetics after Fosfluconazole Administration and Dosing Optimization in Extremely Low-Birth-Weight Infants - Ayano Tanzawa; Jumpei Saito; Kensuke Shoji; Yuka Kojo; Takanori Funaki; Hidehiko Maruyama; Tetsuya Isayama; Yushi Ito; Hidefumi Nakamura; Akimasa Yamatani (Microbiology Spectrum, 2022)
ABSTRACT A prospective single-center study was conducted to characterize the pharmacokinetics (PK) of fluconazole (FLCZ) in extremely low-birth-weight infants (ELBWIs) who received fosfluconazole (F-FLCZ). Intravenous F-FLCZ was administered at a dose of 3 mg/kg of body weight every 72 h during the first 2 weeks of life, every 48 h during the third and fourth weeks of life, and every 24 h after 5 weeks of life. Blood samples from ELBWIs treated with F-FLCZ were collected using scavenged samples. The concentration of FLCZ was determined using liquid chromatography-tandem mass spectrometry. The population pharmacokinetic model was established using Phenix NLME 8.2 software. In total, 18 ELBWIs were included in this analysis. Individual PK parameters were determined by a one-compartment analysis with first-order conversion. Postmenstrual age (PMA), serum creatinine (SCr), and alkaline phosphatase were considered covariates for clearance (CL). The mean population CL and the volume of distribution were 0.011 L/h/kg0.75 and 0.95 L/kg, respectively. Simulation assessments with the final model revealed that the current regimen (3 mg/kg every 72 h) could achieve the proposed target FLCZ trough concentration (>2 μg/mL) in 43.3% and 72.2% of infants with a PMA of ≥37 and 30 to 36 weeks, respectively, and an SCr level of <0.5 mg/dL. Shortened dosing intervals (every 48 or 24 h) might improve the probability of target attainment. This study was the first to assess the PK of F-FLCZ in ELBWI, as well as the first to provide fundamental information about FLCZ exposure after F-FLCZ administration, with the goal of facilitating dose optimization in the ELBWI population. IMPORTANCE Invasive fungal infection is an important cause of mortality and morbidity in very preterm or very-low-birth-weight infants. In order to limit the risk of invasive fungal infections in this population, the administration of fluconazole is generally recommended for extremely low-birth-weight infants admitted to a neonatal intensive care unit with a Candida species colonization prevalence rate of >10%, under the guidelines of the Infectious Diseases Society of America. Fosfluconazole can reduce the volume of solution required for intravenous therapy compared to fluconazole because it has increased solubility, which is a major advantage for infants undergoing strict fluid management. To date, no study has demonstrated the fluconazole pharmacokinetics after fosfluconazole administration in neonates and infants, and this needs to be clarified. Here, we characterized the pharmacokinetics of fluconazole in extremely low-birth-weight infants who received F-FLCZ and explored the appropriate dosage in this patient population.